PERBEDAAN PENGETAHUAN KELUARGA TERHADAP PENGETAHUAN PREHOSPITAL STROKE KELUARGA - Wa Ode Nur Isnah Sabriyati; Silvia Malasari (Medika Respati : Jurnal Ilmiah Kesehatan, 2022)
The high death rate makes the stroke as the second leading cause of death globally after heart disease. The biggest factor for the delay in prehospital stroke management is the lack of knowledge. Cost-effective case handling will be optimal if the emergency handling cases are well organized and well-prepared. Online health education during the COVID-19 pandemic is the right choice to increase family understanding regarding prehospital stroke which leads to the optimization of prompt and precise emergency services. Objective: To determine the effect of online method health education on family stroke prehospital knowledge in Makassar city. Methods: The study was a quasy experiment using two group pretest-posttest design with a control group design. The sample was the community in the working area of the public health center in Makassar, amounting to 15 samples from the intervention group as same with the control group based on the rule of thumb using accidental sampling technique. Result: The mean change in the intervention group was 2.067 and the control group was -0.2. The difference test after treatment was 0.018 (p <0.05). Conclusion: There was an effect of online method health education after intervention.